Peranan ICT dalam Pencapaian Kesuksesan Pelaksanaan Strategi di Perguruan Tinggi Negeri - Okfalisa Okfalisa (UIN Sultan Syarif Kasim Riau, 2012)
Measuring the strategy implementation based on numbers of KPIs (Key Performance Indicators) is no longer adequate. The role of knowledge process is believed to be able to enhance this process through the involvement of stakeholders in solving the strategy implementation problems. To measure this achievement, a new framework has been studied and justified through interviews and surveys conducted within Malaysian Public Higher Education Institution. One of the important indicators proposed in this framework is the role of ICT. A statistical analysis through the application of Confirmatory Factor Analysis (CFA) was shown how ICT can enhance the effectiveness of knowledge process, especially in utilizing knowledge (Knowledge Utilization Activity).This study aids the stakeholders in conducting several improvements and corrective actions towards their strategy implementation success.Keywords: ICT, Knowledge Process, Problem Solving, Strategy Implementation Success